A steady-state target calculation method based on "point" model for integrating processes. (May 2015) - Pang, Qiang; Zou, Tao; Zhang, Yanyan; Cong, Qiumei
Abstract: Aiming to eliminate the influences of model uncertainty on the steady-state target calculation for integrating processes, this paper presented an optimization method based on "point" model and a method determining whether or not there is a feasible solution of steady-state target. The optimization method resolves the steady-state optimization problem of integrating processes under the framework of two-stage structure, which builds a simple "point" model for the steady-state prediction, and compensates the error between "point" model and real process in each sampling interval. Simulation results illustrate that the outputs of integrating variables can be restricted within the constraints, and the calculation errors between actual outputs and optimal set-points are small, which indicate that the steady-state prediction model can predict the future outputs of integrating variables accurately. Highlights: The "point" model is presented to resolve the problem of steady-state target calculation for integrating process. We use a method of compensation to reduce the steady-state error of predictive model in each sampling interval. We also present a method determining whether there is a feasible solution of steady-state target. The optimization method in this paper is still in the framework of two-stage structure whose advantages are reserved.